Optimal Media Mix for IEC Campaigns Using Fuzzy Linguistic Genetic Algorithm: A Study of Swachh Bharat Abhiyan (Clean India Mission) - Sharma, Manu; Joshi, Sudhanshu (Journal of operations and strategic planning, 2019)
Abstract Under ‘Swachh Bharat Abhiyan’ numerous IEC campaigns have launched with multiple media vehicles to achieve an aim of maximizing the awareness level and triggering the mass to adapt behavioral change. Media optimization is a challenging process due to budgetary constraints and multiple media vehicles, but it leads to radical shift in the expenditures as well as in the outcomes. This research study follows two-phase procedure to identify the optimal media mix for IEC Campaigns under ‘Swachh Bharat by applying AHP (Analytical hierarchical process) followed by Fuzzy linguistic genetic algorithms to identify the top 5 media vehicle for IEC campaigns further followed by Fuzzy linguistic genetic algorithms in second phase find the best fit of media insertions with least cost. Both the methods are used in order to find a best fit of cost effective media for promoting the National cleanliness drive ‘Swachh Bharat Abhiyan’. This study is helpful for the stakeholders and decision-makers to plan the IEC campaigns effectively and efficiently.